Blockchain storage:technologies and challenges - Zhenhua CAI; Jiayun LIN; Fang LIU (网络与信息安全学报)
Blockchain′s characteristics of non-temper and decentralization can be utilized to improve the data security and scalability of storage systems,called blockchain storage.These works that combine storage with blockchain technology,are mainly divided into three categories:decentralized storage systems based on blockchain,improve the performance of existing storage systems based on blockchain,and the underlying storage strategies of blockchain.These works were summarized,the current blockchain storage systems were compared,the main challenges that blockchain and storage being facing were discussed and its future development was forecasted.